THE SCHOOLS’ MANUSCRIPTS COLLECTION PROVERBS OF IRELAND AND THEIR DIGITIZATION - Carson Williams, Fionnuala (Proverbium - Yearbook, 2018)
A large collection of contemporaneous folklore from Ireland has recently become available online. It contains thousands of proverbs, mainly in lists but some in various kinds of narrative and some with explanations. The article below outlines the background to the collection, the main concerns and contents of the proverbs and how to access them. The collection is being transcribed and these transcriptions are word or even proverb-searchable.